Proses Kreatif Iklan televisi Simpati Ektra Versi Mertua - Dwi Irmawaty Gultom; Jefri Roberto Gala (Universitas Mercu Buana, 2008)
Ad competition mobile operators currently uery tight, each mobile operator to qff'er the product through 60!h the teleuision media, radio and print media to attract audiences. Aduertising through the medium of teleuision to make a wider range of broadcasting and makes the characters become more dime. Inept, TPOseqfthisstttd!liraorderto knowthestttge^of the creatiueprocess ofSimpotiEkstra